Chapter Prodromi dell'alternanza scuola-lavoro: la Ferme École di Meleto in Val d'Elsa - XODO, CARLA (Studies on Adult Learning and Education, 2022)
The contribution reconstructs the work of innovation carried out by Cosimo Ridolfi in the Agricultural Institute of Meleto in Val d'Elsa, as a paradigmatic example of the relationship between theory and practice and a model example of school-work alternation. Through a historical perspective, we want to highlight the educational aspects of practical and conceptual activity in practical and operational contexts, especially in agriculture, a tradition inaugurated by Ridolfi and continued by Lambruschini, which initiated a true Tuscan school of innovation in the formal learning setting of education and training that has become a European model.